A Student Mock Trial in Forensic Linguistics - Breen, Joshua; Keaton, Ashley; Juárez, Carolina; McMenamin, Gerald; Mohundro, Jacob; Mora, Jared; Nieves, Josué; Tan, Annette (Language and Law / Linguagem e Direito, 2020)
We review our preparation and production of a mock trial designed to give students experience as expert witnesses in forensic linguistics. As part of a senior seminar in Spanish linguistics, students made all pre-trial preparations and presented testimony for a real-world case related to the meaning of the Spanishlanguage nickname negrito. The trial took place in the Model Courtroom of The National Judicial College on the campus of the University of Nevada, Reno. The courtroom setting included judge, counsel for the plaintiff and defense, bailiff, a court-certified Spanish-English interpreter, eight student expert-witnesses, and numerous student and faculty observers. This paper is structured to present four aspects of the trial: the instant case; pretrial preparation of all linguistic issues; testimony presented; and student perspectives on the experience of testifying and subsequently presenting this project at a linguistics conference.